ZAKAT SEBAGAI SUMBER PENINGKATAN KEMANDIRIAN FISKAL DI PROVINSI ACEH - Diana Febriani Hasibuan; Miksalmina Miksalmina; Zulkifli Zulkifli (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2021)
AbstractThis study aims to determine the contribution of zakat and economic growth in increasing fiscal independence in Aceh Province in 2015-2019. The study used secondary data, consisting of zakat realization, economic growth, and fiscal independence. It used multiple linear regression method and chose a random effects model approach (Random Effect). This study found that zakat and economic growth positively and significantly affect fiscal independence in Aceh Province in 2015-2019. Therefore, local governments can increase fiscal independence through socialization to the community to pay their zakat through Baitul Mal. This will increase own source revenue and increasing the fiscal capacity of Aceh in conducting development. Thus, local government should maintain the level of economic growth through increasing the production of goods and services in Aceh Province.